Book Review of The Murder of Roger Ackroyd - Prihatiningsih, Reni (LANTERN (Journal on English Language, Culture and Literature), 2015)
Prose, poetry and drama are categories of literary works. Those categories consist of two genres, fiction and nonfiction. Novel is one of the fiction categories of literary works. Novel has more attractive than other literary works because it tells the story about human life that may happen in the reality. That reason makes the readers easy to understand the story in a novel.